Acute ischemic stroke patients with diffusion-weighted imaging-Alberta Stroke Program Early Computed Tomography Score ≤ 5 can benefit from endovascular treatment: a single-center experience and literature review. - Song, Kangping; Guan, Min; Li, Wenxian; Jing, Zhen; Xie, Xiaomei; Shi, Changzheng; Liang, Jianye; Qiao, Hongyu; Huang, Li'an (Neuroradiology, 2019)
Purpose: The recommendation strength of the guidelines for mechanical thrombectomy among patients with large pre-treatment core infarct is weak. We evaluated the safety and outcome of endovascular treatment for acute ischemic stroke with diffusion-weighted imaging-Alberta Stroke Program Early Computed Tomography Score (DWI-ASPECTS) ≤ 5.Methods: Data on acute ischemic stroke patients with DWI-ASPECTS ≤ 5 who underwent endovascular treatment within 6 h, or presented an arterial spin labeling-DWI (ASL-DWI) mismatch within 12 h, at our center were retrospectively collected. We report the clinical characteristics and outcome of every patient, and review the relevant literature.Results: Among the 19 patients who were enrolled, all experienced successful reperfusion, and 10 achieved a favorable outcome (modified Rankin scale (mRS) ≤ 2). Two patients presented with symptomatic intracranial hemorrhage (sICH); both of them had a poor outcome (mRS > 2).Conclusion: Acute ischemic stroke patients with large DWI lesions caused by large vessel occlusion can achieve a favorable clinical outcome with endovascular treatment if recanalization is performed within 6 h, or after 6 h in case of an ASL-DWI mismatch.